Patellofemoral Chondromalacia Does Not Influence Radiographic and Clinical Outcomes following High Tibial Osteotomy - Kim, You Keun; Yoo, Jae Doo; Oh, Minjoon; Cho, Euihwan; Kim, Nam Ki (The Journal of Knee Surgery, 2019)
Effect of patellofemoral (PF) chondromalacia on results of high tibial osteotomy (HTO) has not been identified. Therefore, the objective of the present study was to analyze the effect of PF chondromalacia on relatively short-term radiographic and clinical outcomes of HTO. Patients who underwent open wedge HTO (OWHTO) from February 2010 to January 2015 were enrolled. A total of 101 knees were divided into two groups: 56 knees without PF chondromalacia in group A, while 45 knees with PF chondromalacia extended to subchondral bone in group B. Radiologic outcomes were compared using mechanical tibiofemoral angle, ratio of weight-bearing line (WBL), and minimal joint space width of the lateral compartment. Clinical outcomes were compared using range of motion in affected knee, visual analog scale, modified Lysholm score, and Kujala score. The mean mechanical tibiofemoral angle was 4.6 degree in group A and 4.8 degree in group B. The mean ratio of WBL was 63.8% in group A and 63.6% in group B at final. The mean minimum joint space width of the lateral compartment was 5.8 mm in group A and 5.8 mm in group B on standing AP radiograph. It was 5.3 mm in group A and 5.4 mm in group B on Rosenburg view at final. The mean ROM was 137.2 degree in group A and 137.5 degree in group B. The mean visual analog scale was 2.1 in group A and 2.3 in group B at final. The mean modified Lysholm score was 90.6 in group A and 89.1 in group B at final. The mean Kujala score was 90.2 in group A and 89.1 in group B at final. PF chondromalacia does not influence short-term radiographic and clinical outcomes following OWHTO.
Keywords: osteoarthritis; chondromalacia; high tibial osteotomy